Structure of Full-Length Human PDGFRβ Bound to Its Activating Ligand PDGF-B as Determined by Negative-Stain Electron Microscopy. Issue 24 (4th December 2015) - Chen, Po-Han; Unger, Vinzenz; He, Xiaolin
Abstract: Members of the receptor tyrosine kinases (RTKs) regulate important cellular functions such as cell growth and migration, which are key steps in angiogenesis, in organ morphogenesis and in the unregulated states, cancer formation. One long-standing puzzle regarding RTKs centers on how the extracellular domain (ECD), which detects and binds to growth factors, is coupled with the intracellular domain kinase activation. While extensive structural works on the soluble portions of RTKs have provided critical insights into RTK structures and functions, lack of a full-length receptor structure has hindered a comprehensive overview of RTK activation. In this study, we successfully purified and determined a 27-Å-resolution structure of PDGFRβ [a full-length human platelet-derived growth factor receptor], in complex with its ligand PDGF-B. In the ligand-stimulated complex, two PDGFRβs assemble into a dimer via an extensive interface essentially running along the full-length of the receptor, suggesting that the membrane-proximal region, the transmembrane helix and the kinase domain of PDGFRβ are involved in dimerization. Major structural differences are seen between the full-length and soluble ECD structures, rationalizing previous experimental data on how membrane-proximal domains modulate receptor ligand-binding affinity and dimerization efficiency. Also, in contrast to the 2-fold symmetry of the ECD, the intracellular kinase domains adopt an asymmetric dimer arrangement, in agreement with prior observations for the closely related KIT receptor. In essence, the structure provides a first glimpse into how platelet-derived growth factor receptor ECD, upon ligand stimulation, is coupled to its intracellular domain kinase activation. Graphical abstract: Highlights: Full-length transmembrane RTK structures are currently lacking. Purification and visualization of platelet-derived growth-factor-stimulated full-length PDGFRβ by electron microscopy. Domain organizations that differ from crystal structures of soluble domains. Asymmetric kinase domain dimer arrangement in full-length receptor. Demonstration of extracellular coupling with intracellular kinase activation.